Sharing Experiences in Infancy: From Primary Intersubjectivity to Shared Intentionality - Moll, Henrike; Pueschel, Ellyn; Ni, Qianhui; Little, Alexandra (Frontiers in Psychology, 2021)
We contrast two theses that make different assumptions about the developmental onset of human-unique sociality. The primary intersubjectivity thesis (PIT) argues that humans relate to each other in distinct ways from the beginning of life, as is shown by newborns’ participation in face-to-face encounters or “primary intersubjectivity”. According to this thesis, humans’ innate relational capacity is the seedbed from which all subsequent social-emotional and social-cognitive developments continuously emerge. The shared intentionality thesis (SIT) states that human-unique forms of interaction develop at 9-12 months of age, when infants put their heads together with others in acts of object-focused joint attention and simple collaborative activities. According to this thesis, human-unique cognition emerges rapidly with the advent of mind-reading capacities that evolved specifically for the purpose of coordination. In this paper, we first contrast the two theses and then sketch the outlines of an account that unifies their strengths. This unified account endorses the PIT’s recognition of the fundamental importance of primary intersubjectivity. Any act of sharing experiences is founded on the communicative capacity that is already displayed by young infants in primary intersubjectivity. At the same time, we question the PIT’s interpretation that dyadic encounters have the triadic structure of joint attention. Lastly, we draw on empirical work on the development of joint attention, imitation, and social referencing that serves as evidence that primary intersubjectivity continuously unfolds into the capacity for triadic joint attention.